Playful architecture - Constructing sociality - Van, Wyngaarden Katherine (School of Architecture, Planning and Geomatics, 2023)
This thesis explores themes of playful architecture, and how activated, adaptable, and dynamic spaces can be created through embracing the inherent instability of social space. The exploration focuses on the social aspects of space and on an architecture that is capable of encouraging connection and interaction, an architecture that can adapt and promote skills development and sharing, and an architecture that provides identity – one that acts as an attractor rather than an object. Social spaces are unpredictable and dynamic in the interactions and the events that it allows for. Spaces are also full of paradoxes - of disjunction between space and event. This means that architecture and space is constantly unstable and on the verge of change. It is these dynamic and chaotic elements that, if held properly, allow for social, creative, and playful spaces and events. The project is situated within an imagined future fabric of District 6 in Cape Town, on a site with existing activities to be plugged into and reinforced. This site also allowed for a testing of how a playful architecture, that is community and socially driven, sits within the developing context of South Africa. The programme revolves around a city living room which is a training centre providing spaces for working, learning, and engaging as well as offering accessible social hubs that act as social filters, allowing users in and around the site to gather, wait and interact.